EFEKTIVITAS MINYAK BIJI Jatropha curcas MENGENDALIKAN KEPIK PENGHISAP POLONG KEDELAI Nezara viridula (HEMIPTERA: PENTATOMIDAE) DI RUMAH KASA - Asmanizar Asmanizar; Aldywaridha Aldywaridha; Edy Sumantri; Ardiansyah Putra Damanik (Jurnal Agrotek Tropika, 2020)
Green Stink Bug Nezara viridula (Hemiptera: Pentatomidae) is an important pest on soybean. The yield losses could be qualitatively and quantitatively. Controlling by using synthetic insecticide caused negative impact. Hence, controlling by using botanical insecticide was as an alternative. The study was conducted at wire house, to know the effect of J. curcas seed oil concentration on N. viridula mortality, pod damaged, empty pod, seed damaged and dry seed weight. The J. curcas seed oil was obtained by Soxhlet Extractor. The concentration of J. curcas seed oil as the treatment, viz. 0% (control); 0.125; 0.25 dan 0.5% (volume oil/volume solution,v/v), and the water as solution applied on soybean plant which was infested of ten N. viridula adult. The result showed all variable observed affected by J. curcas seed oil concentration. The 0.25 and 0.5% concentration showed the mortality reached 95.0 and 100% at 6 days after treatment, while,  pod damaged was 7.34 and 1.84%; empty pod was 25.32%, seed damaged was 3.72 and 0.78% and weight of dry seed was 9.94 and 10.44 g.  The weight of dry seed at control treatment was 5.52 g. The J. curcas seed oil at 0.5% of concentration has a potency to control N. viridula on soybean plant. There is a need further study to know the effectivity on soybean in the field.